Dialectics of Spontaneity The Aesthetics and Ethics of Su Shi (1037-1101) in Poetry - Yang, Zhiyi (Sinica Leidensia, 2015)
In Dialectics of Spontaneity, Zhiyi Yang examines the aesthetic and ethical theories of Su Shi, the primary poet, artist, and statesman of Northern Song. Readership: All interested in Chinese literature, aesthetics and ethics, in particular Su Shi, in the comparative discussion about spontaneity, and those concerned with the reception history of Tao Qian or with inner alchemy.